Al-ti-c-sr grain refiner and method for preparing the same

CN117867313BActive Publication Date: 2026-10-13合肥波林新材料股份有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311868503.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2026-10-13
Estimated Expiration
2043-12-28

AI Technical Summary

Technical Problem

专利CN109055792A(一种制备Al-Ti-C中间合金的方法)中采用氟钛酸钾和石墨粉在高温铝中熔盐反应制备Al3Ti和TiC,所制备的Al3Ti在10-20μm之间,TiC颗粒尺寸在1-1.5μm之间,其所得产品仍存在TiC颗粒尺寸较大的问题

Benefits of technology

[0020](1)本发明为了增加石墨与铝之间的反应性能,一方面,通过使用镀铜石墨粉以增强石墨与Al间的润湿性,提高石墨与Al之间的结合性能;原理在于石墨粉是非金属材料,与金属之间的润湿性不好,石墨表面镀铜之后,通过中间体铜与Al结合更好,这样间接增强了石墨与Al之间的结合;另一方面,通过增加放电等离子烧结炉烧结工序,并在混合粉末中预先加入Al粉,使镀铜石墨粉与Al之间形成扩散烧结的效果,使其在后续反应中能够更好的进行反应,通过提高熔体反应的效率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117867313B_ABST
    Figure CN117867313B_ABST
Patent Text Reader

Abstract

The application discloses an Al-Ti-C-Sr grain refiner and a preparation method thereof, and the preparation method comprises the following steps: adding Al powder, K2TiF6, NaCl, copper-plated graphite powder and Sr powder into a dispersant, uniformly mixing to obtain a mixture; drying the mixture to obtain a mixed powder, compressing the mixed powder into a block sample, preheating the block sample to obtain a preheated sample; placing the preheated sample into a spark plasma sintering furnace to perform sintering, obtaining a preform; heating a pure aluminum block to melt the pure aluminum block to obtain molten aluminum; adding the preform into the molten aluminum and uniformly mixing to obtain a mixed material; after the mixed material is treated by heat preservation, the surface dross of the mixed material is fished out, then the mixed material is poured into a mold to form a target product. The preparation method has the advantages of simple preparation equipment, short process flow, high preparation efficiency and the like, and the prepared Al-Ti-C-Sr grain refiner has better grain refining effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal material manufacturing technology, specifically relating to an Al-Ti-C-Sr grain refiner and its preparation method. Background Technology

[0002] With the continuous increase in global car ownership, the energy-saving and emission-reducing effects of automotive lightweighting have become increasingly recognized, especially with the development of new energy vehicles, which have higher expectations for lightweighting. Aluminum alloys are widely recognized in the industry as the most promising metal material for automotive lightweighting. Aluminum alloys have the characteristics of low density, light weight, corrosion resistance, good processability, and recyclability. While achieving the same mechanical performance indicators, they can reduce the weight by 60% compared to traditional steel materials; under the same impact conditions, aluminum alloy sheets absorb 50% more impact energy than steel sheets. Based on these excellent properties, aluminum alloy materials have been widely used in automobiles, expanding from initial engine blocks, transmission housings, and wheel hubs to various important components of the vehicle body. In 1976, the aluminum alloy used in each car produced in the United States was only 39 kg; in 1982, this reached 62 kg, and in 1998, it reached 100 kg. Currently, developed countries use up to 138 kg of aluminum in automobiles, with an aluminum content of 12%. However, the use of aluminum in automobiles in my country lags far behind that of foreign countries, with an average aluminum content of only 60 kg and an aluminum content of less than 5%.

[0003] However, the poor mechanical properties of aluminum alloys limit their industrial application. Improving the mechanical properties of aluminum-titanium-carbon alloys by adding grain refiners has become a research hotspot. Grain refinement is one of the important methods to improve the mechanical properties of aluminum and its alloys, reduce segregation, and improve the density of castings.

[0004] Studies have shown that the grain refinement effect of aluminum-titanium-carbon master alloys is mainly affected by TiC; the smaller the TiC size, the better the grain refinement effect on the aluminum alloy. In recent years, many researchers have adopted various methods to prepare aluminum-titanium-carbon master alloys. Patent CN109055792A (a method for preparing Al-Ti-C master alloys) uses potassium fluorotitanate and graphite powder in a high-temperature molten salt reaction to prepare Al3Ti and TiC. The prepared Al3Ti particles are between 10-20 μm in size, and the TiC particles are between 1-1.5 μm in size. However, the resulting product still suffers from the problem of relatively large TiC particle size. Preparing smaller TiC particles to improve the grain refinement effect of aluminum alloys is an urgent problem to be solved in automotive aluminum materials. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide an Al-Ti-C-Sr grain refiner capable of refining TiC particles and its preparation method. This invention uses potassium fluorotitanate, copper-plated graphite powder, sodium chloride, and strontium powder as main raw materials. These materials are pressed into blocks and preheated, then sintered in a spark plasma sintering furnace to form a preform. The preform is then added to molten aluminum in a high-temperature pit furnace using an in-situ reaction method to prepare the final product. Ultrasonic stirring is applied during this process to enhance the uniformity of solute distribution, ultimately yielding an Al-Ti-C-Sr grain refiner with good grain refining effect. This preparation method has advantages such as simple equipment, short process flow, and high preparation efficiency, and the prepared Al-Ti-C-Sr grain refiner exhibits better grain refining effect.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing an Al-Ti-C-Sr grain refiner includes the following steps:

[0008] (1) Add graphite powder to ethanol and stir ultrasonically for 10 min to obtain a mixture; add Tween 60, Cu(NO3)2·3H2O and C6H to the mixture. 12 O6·H2O was stirred for 2 hours, then dried, washed, and dried again to obtain copper-plated graphite powder.

[0009] (2) Add Al powder, K2TiF6, NaCl, copper-plated graphite powder, and Sr powder to the dispersant. First, mechanically stir, then ultrasonically disperse to obtain a mixture; (Al powder, copper-plated graphite powder, and Sr powder are preforms. Al powder can be sintered with copper-plated graphite powder in a plasma sintering furnace in advance, and can also be sintered with Sr powder. This is a pre-bonding process, which results in better dispersion in step 5. Sr is actually a rare earth element, which is beneficial for the chemical formation of TiC in step 5. In addition, Sr also has a certain grain refiner effect, which can better play the role of grain refiner.)

[0010] (3) After drying the mixture, a mixed powder is obtained, and the mixed powder is pressed into a block; then it is preheated to obtain a preheated sample;

[0011] (4) The preheated sample is placed in a spark plasma sintering furnace for sintering to obtain a preform. The purpose of spark plasma sintering is to premix the various materials, especially to enable the Al powder to form a diffusion sintering effect with the copper-plated graphite powder, so that it can react better in the subsequent reaction.

[0012] (5) Heat the pure aluminum block to a certain temperature to melt it to obtain molten aluminum. Add the preform in step (4) to the molten aluminum, and perform mechanical stirring and ultrasonic stirring to make it evenly mixed. After keeping it warm for 30 minutes, remove the surface scum and pour it into a mold to form Al-Ti-C-Sr grain refiner.

[0013] As a preferred technical solution, the dispersant in step (2) is ethanol; the mass ratio of Al powder, K2TiF6, NaCl, copper-plated graphite powder and Sr powder is 40-50:20-30:10-15:5-10:2-3.

[0014] As a preferred technical solution, the pressing pressure in step (3) is 50-200MPa, such as 50MPa, 100MPa or 200MPa.

[0015] As a preferred technical solution, in step (4), the temperature inside the discharge plasma sintering furnace is 800℃-1000℃, the pressure is 12-18MPa, and the sintering time is 2min. During the sintering process, the pressure inside the discharge plasma sintering furnace must be strictly controlled. If the pressure is too low, it will lead to insufficient sintering, and if the pressure is too high, it will lead to over-sintering.

[0016] As a preferred technical solution, the melt temperature in step (5) is 1000-1200℃, and the mold is made of iron or copper.

[0017] As a preferred technical solution, in step (5), the ultrasonic stirring has a power of 500W and a stirring time of 5-20min.

[0018] A second objective of this invention is to provide an aluminum-titanium-carbon alloy grain refiner prepared by the above-described preparation method, wherein the aluminum-titanium-carbon alloy grain refiner comprises Al and TiC particles, and the size of the TiC particles is 10-100 nm.

[0019] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0020] (1) In order to increase the reactivity between graphite and aluminum, this invention uses copper-plated graphite powder to enhance the wettability between graphite and Al and improve the bonding performance between graphite and Al. The principle is that graphite powder is a non-metallic material and has poor wettability with metals. After copper plating on the graphite surface, the bonding between graphite and Al is better through the intermediate copper, thus indirectly enhancing the bonding between graphite and Al. On the other hand, by adding a spark plasma sintering furnace sintering process and pre-adding Al powder to the mixed powder, a diffusion sintering effect is formed between the copper-plated graphite powder and Al, so that it can react better in subsequent reactions and improve the efficiency of melt reaction.

[0021] (2) The mixed powder prepared in this invention contains Al powder, K2TiF6, NaCl, copper-plated graphite powder, and Sr powder. The materials are readily available and inexpensive. In the subsequent reaction, when the preform is added to molten aluminum, K2TiF6 decomposes to generate Ti element which enters Al, and copper-plated graphite powder also enters Al. In the high-temperature molten aluminum environment, Ti and graphite generate TiC. Copper-plated graphite allows graphite to enter Al more effectively. Sr powder is added at this time to improve the generation effect of this process. Cu and Sr will remain in the final grain refiner, but in very small amounts. Cu reacts with Al to generate Al2Cu intermediate compound, which has a good effect on improving the hardness and strength of the material. Sr is a rare earth element that can refine grains, improve the strength and hardness of the material, and also improve the performance of the material.

[0022] (3) The present invention uses two mixing methods, mechanical stirring and ultrasonic stirring, to mix the materials, which can prevent TiC particles from agglomerating in Al melt; ultrasonic stirring in the present invention can promote the formation efficiency of TiC and reduce its size, and has a significant effect on improving the effect of the finer agent. Attached Figure Description

[0023] Figure 1 The image shows the microstructure of the Al-Ti-C-Sr grain refiner prepared in Example 1.

[0024] Figure 2 The image shows the microstructure of the Al-Ti-C-Sr grain refiner prepared in Example 2. Detailed Implementation

[0025] The present invention will be further described below with reference to embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.

[0026] Detection methods

[0027] After the sample was sanded on sandpaper, it was polished on a polishing machine. The microstructure and morphology of the material were observed under a scanning electron microscope with a magnification of 10,000 to 100,000 times. The equipment used was a Zeiss Sigma 300 model.

[0028] Example 1

[0029] A method for preparing an Al-Ti-C-Sr grain refiner includes the following steps:

[0030] (1) At an ambient temperature of 25℃, 5g of graphite powder was added to 500ml of ethanol and stirred ultrasonically for 10min; 5g of Tween 60, 80g of Cu(NO3)2·3H2O and 50g of C6H were added to the mixture. 12 O6·H2O was stirred for 2 hours. The mixed powder was then dried, washed with deionized water, and dried again to obtain copper-plated graphite powder.

[0031] (2) Weigh the following substances by mass percentage: 50g of Al powder, 30g of K2TiF6, 10g of NaCl, 8g of copper-plated graphite powder, and 2g of Sr powder. Then add them to 300ml of ethanol and mechanically stir at 280rpm for 30min. Then continue ultrasonic stirring for 15min at an ultrasonic power of 500W to obtain a mixture.

[0032] (3) Place the mixture in an oven and keep it at 100°C for 2 hours to dry it and obtain a mixed powder. Press the mixed powder into a block sample under a pressure of 50 MPa. Place the block sample in a 200°C environment for 2 hours to preheat it and obtain a preheated sample.

[0033] (4) Place the sample obtained in (3) into a spark plasma sintering furnace and sinter at 800℃ and 12MPa for 2 minutes before taking it out.

[0034] (5) Heat the pure aluminum block to 1000℃ and keep it warm. Add the sintered sample from step (4) to the molten aluminum and perform mechanical stirring and ultrasonic stirring to make it evenly mixed. The ultrasonic stirring power is 500W and the time is 10min. After removing the surface slag, pour it into the mold to form Al-Ti-C-Sr alloy.

[0035] After grinding and polishing, the product obtained in Example 1 was observed using a scanning electron microscope. The product contained a large number of TiC particles, uniformly distributed between Al grains, with a size of 10-100 nm. Figure 1 As shown.

[0036] Example 2

[0037] A method for preparing an Al-Ti-C-Sr grain refiner includes the following steps:

[0038] (1) At an ambient temperature of 25℃, 5g of graphite powder was added to 500ml of ethanol and stirred ultrasonically for 10min; 5g of Tween 60, 80g of Cu(NO3)2·3H2O and 50g of C6H were added to the mixture. 12 O6·H2O was stirred for 2 hours. The mixed powder was then dried, washed with deionized water, and dried again to obtain copper-plated graphite powder.

[0039] (2) Weigh the following substances by mass percentage: 50g of Al powder, 25g of K2TiF6, 15g of NaCl, 8g of copper-plated graphite powder, and 2g of Sr powder. Then add them to 300ml of ethanol and mechanically stir at 280rpm for 30min. Then continue ultrasonic stirring for 15min at an ultrasonic power of 500W to obtain a mixture.

[0040] (3) Place the mixture in an oven and keep it at 100°C for 2 hours to dry it and obtain a mixed powder. Press the mixed powder into a block sample under a pressure of 50 MPa. Place the block sample in a 200°C environment for 2 hours to preheat it and obtain a preheated sample.

[0041] (4) Place the sample obtained in (3) into a spark plasma sintering furnace and sinter at 800℃ and 12MPa for 2 minutes before taking it out.

[0042] (5) Heat the pure aluminum block to 1000℃ and keep it warm. Add the sintered sample from step (4) to the molten aluminum and perform mechanical stirring and ultrasonic stirring to make it evenly mixed. The ultrasonic stirring power is 500W and the time is 10min. After removing the surface slag, pour it into the mold to form Al-Ti-C-Sr alloy.

[0043] After grinding and polishing, the product obtained in Example 2 was observed using a scanning electron microscope. The product contained a large number of TiC particles, uniformly distributed between Al grains, with a size of 10-100 nm. Figure 2 As shown.

[0044] Example 3

[0045] A method for preparing an Al-Ti-C-Sr grain refiner includes the following steps:

[0046] (1) At an ambient temperature of 25℃, 5g of graphite powder was added to 500ml of ethanol and stirred ultrasonically for 10min; 5g of Tween 60, 80g of Cu(NO3)2·3H2O and 50g of C6H were added to the mixture. 12 O6·H2O was stirred for 2 hours. The mixed powder was then dried, washed with deionized water, and dried again to obtain copper-plated graphite powder.

[0047] (2) Weigh the following substances by mass percentage: 50g of Al powder, 25g of K2TiF6, 15g of NaCl, 8g of copper-plated graphite powder, and 2g of Sr powder. Then add them to 300ml of ethanol and mechanically stir at 280rpm for 30min. Then continue ultrasonic stirring for 15min at an ultrasonic power of 500W to obtain a mixture.

[0048] (3) Place the mixture in an oven and keep it at 100°C for 2 hours to dry it and obtain a mixed powder. Press the mixed powder into a block sample under a pressure of 50 MPa. Place the block sample in a 200°C environment for 2 hours to preheat it and obtain a preheated sample.

[0049] (4) Place the sample obtained in (3) into a spark plasma sintering furnace and sinter it for 2 minutes at 1000℃ and 18MPa pressure.

[0050] (5) Heat the pure aluminum block to 1000℃ and keep it warm. Add the sintered sample from step (4) to the molten aluminum and perform mechanical stirring and ultrasonic stirring to make it evenly mixed. The ultrasonic stirring power is 500W and the time is 10min. After removing the surface slag, pour it into the mold to form Al-Ti-C-Sr alloy.

[0051] After grinding and polishing, the product obtained in Example 3 was observed by scanning electron microscopy. A large number of TiC particles were found in the product, which were uniformly distributed between Al grains and had a size of 10-100 nm.

[0052] Example 4

[0053] A method for preparing an Al-Ti-C-Sr grain refiner includes the following steps:

[0054] (1) At an ambient temperature of 25℃, 5g of graphite powder was added to 500ml of ethanol and stirred ultrasonically for 10min; 5g of Tween 60, 80g of Cu(NO3)2·3H2O and 50g of C6H were added to the mixture. 12 O6·H2O was stirred for 2 hours. The mixed powder was then dried, washed with deionized water, and dried again to obtain copper-plated graphite powder.

[0055] (2) Weigh the following substances by mass percentage: 50g of Al powder, 25g of K2TiF6, 15g of NaCl, 8g of copper-plated graphite powder, and 2g of Sr powder. Then add them to 300ml of ethanol and mechanically stir at 280rpm for 30min. Then continue ultrasonic stirring for 15min at an ultrasonic power of 500W to obtain a mixture.

[0056] (3) Place the mixture in an oven and keep it at 100°C for 2 hours to dry it and obtain a mixed powder. Press the mixed powder into a block sample under a pressure of 150 MPa. Place the block sample in a 200°C environment for 2 hours to preheat it and obtain a preheated sample.

[0057] (4) Place the sample obtained in (3) into a spark plasma sintering furnace and sinter it for 2 minutes at 1000℃ and 18MPa pressure.

[0058] (5) Heat the pure aluminum block to 1000℃ and keep it warm. Add the sintered sample from step (4) to the molten aluminum and perform mechanical stirring and ultrasonic stirring to make it evenly mixed. The ultrasonic stirring power is 500W and the time is 20min. After removing the surface slag, pour it into the mold to form Al-Ti-C-Sr alloy.

[0059] As can be seen from the above embodiments, by rapidly increasing the melt temperature, the TiC particle size was reduced from 100-200 nm to 10-100 nm, achieving controllable preparation of TiC particles. Furthermore, SEM microscopic images show that the prepared TiC particles are uniformly distributed and show no agglomeration, which will have a good effect on refining aluminum alloys.

[0060] Comparative Example 1:

[0061] A method for preparing a grain refiner for aluminum-titanium-carbon alloys used in automobiles, comprising the following steps:

[0062] The difference between Comparative Example 1 and Example 1 is that the formula in step (2) is 70g of Al powder, 10g of K2TiF6, 10g of NaCl, 8g of copper-plated graphite powder, and 2g of Sr powder.

[0063] After grinding and polishing, the product obtained in Comparative Example 1 was observed by scanning electron microscopy. The product contained few TiC particles, and the formation efficiency was greatly reduced. The content of K2TiF6 was too low, which could not provide enough Ti elements, resulting in less TiC formation.

[0064] Comparative Example 2:

[0065] A method for preparing a grain refiner for aluminum-titanium-carbon alloys used in automobiles, comprising the following steps:

[0066] The difference between Comparative Example 2 and Example 1 is that the melt temperature in step (5) is 800°C;

[0067] After grinding and polishing, the product obtained in Comparative Example 2 was observed by scanning electron microscopy, and no TiC particles were found in the product.

[0068] Comparative Example 3

[0069] Compared with Example 1, the difference in this comparative example is that the preparation step of copper-plated graphite powder in step (1) is omitted, and graphite powder is used to replace the copper-plated graphite powder in step (2). All other process conditions are the same as in Example 1.

[0070] After grinding and polishing, the product obtained in Comparative Example 3 was observed by scanning electron microscopy. It was found that TiC agglomerated on the grain boundaries of Al grains and did not form a well-dispersed structure.

[0071] Comparative Example 4

[0072] Compared with Example 1, the difference in this comparative example is that Al powder was not added in step (2), while other process conditions are the same as in Example 1.

[0073] After grinding and polishing, the product obtained in Comparative Example 4 was observed by scanning electron microscopy, and it was found that the amount of TiC generated was relatively small.

[0074] Comparative Example 5

[0075] Compared with Example 1, the difference in this comparative example is that Sr powder was not added in step (2), while other process conditions are the same as in Example 1.

[0076] After grinding and polishing, the product obtained in Comparative Example 5 was observed using a scanning electron microscope, which revealed that the content of TiC particles was relatively low.

[0077] Comparative Example 6

[0078] Compared with Example 1, the difference in this comparative example is that step (4) is omitted, and the preheated sample obtained in step (3) is directly subjected to the operation in step (5). All other process conditions are the same as in Example 1.

[0079] After grinding and polishing, the product obtained in Comparative Example 6 was observed by scanning electron microscopy, and it was found that the amount of TiC particles generated was relatively small.

[0080] The above description of the embodiments is provided to enable those skilled in the art to understand and apply the present invention. It will be apparent to those skilled in the art that various modifications can be made to the embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the embodiments described herein, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A method for preparing an Al-Ti-C-Sr grain refiner, characterized in that, Includes the following steps: Al powder, K2TiF6, NaCl, copper-plated graphite powder, and Sr powder are added to a dispersant. The mixture is first mechanically stirred and then ultrasonically dispersed to obtain a mixture. The mass ratio of Al powder, K2TiF6, NaCl, copper-plated graphite powder, and Sr powder is 40-50:20-30:10-15:5-10:2-3. The mixture is dried to obtain a mixed powder, which is then pressed into a block sample and preheated to obtain a preheated sample. The preheated sample is placed in a spark plasma sintering furnace for sintering to obtain the preform. Pure aluminum blocks are heated to melt them to obtain molten aluminum; the temperature of the molten aluminum is 1000-1200℃; a preform is added to the molten aluminum and mixed evenly to obtain a mixture; after heat preservation treatment, the scum on the surface of the mixture is removed, and then it is poured into a mold to form the target product.

2. The method for preparing the Al-Ti-C-Sr grain refiner according to claim 1, characterized in that, The copper-plated graphite powder is prepared by dispersing graphite powder in ethanol to obtain a mixture, and then adding Tween 60, copper salt and C6H to the mixture. 12 O6·H2O is thoroughly stirred and then dried. After washing, it is dried again to obtain copper-plated graphite powder.

3. The method for preparing the Al-Ti-C-Sr grain refiner according to claim 2, characterized in that, The dispersant is ethanol; the copper salt is copper nitrate.

4. The method for preparing the Al-Ti-C-Sr grain refiner according to claim 1, characterized in that, The pressing pressure is 50-200 MPa.

5. The method for preparing the Al-Ti-C-Sr grain refiner according to claim 1, characterized in that, The temperature inside the discharge plasma sintering furnace is 800℃-1000℃, and the pressure is 12-18MPa.

6. The method for preparing the Al-Ti-C-Sr grain refiner according to claim 1, characterized in that, The mold is made of iron or copper.

7. The method for preparing the Al-Ti-C-Sr grain refiner according to claim 1, characterized in that, The method for adding the preform to molten aluminum and mixing it uniformly is to subject it to mechanical stirring and ultrasonic stirring.

8. An Al-Ti-C-Sr grain refiner, characterized in that, It is prepared by the preparation method as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Method for preparing Al-Ti-C intermediate alloy

    CN109055792A

  • Method for preparing refiner for aluminium-titan-carbon-strontium alloy

    CN101338381A

  • Aluminum-titanium-carbon alloy grain refiner and preparation method thereof

    CN112899512A